2005
DOI: 10.1175/ei135.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Soil Changes Following Selective Logging in an Eastern Amazon Forest

Abstract: In the Brazilian Amazon, selective logging is second only to forest conversion in its extent. Conversion to pasture or agriculture tends to reduce soil nutrients and site productivity over time unless fertilizers are added. Logging removes nutrients in bole wood, enough that repeated logging could deplete essential nutrients over time. After a single logging event, nutrient losses are likely to be too small to observe in the large soil nutrient pools, but disturbances associated with logging also alter soil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
5
33
0
1
Order By: Relevance
“…Therefore, a disproportionate increase in larger gaps can be expected to slow overall forest recovery rates and thus will have long-lasting effects on a wide range of ecological processes from carbon cycling to faunal dynamics (16,30,31). These results also highlight the value of reduced-impact logging operations that tend to minimize initial canopy damage levels and thus are more conducive to an expeditious reestablishment of ecosystem functions (15,27,32). Low-impact or low-volume logging also leaves the forest with fewer and smaller canopy gaps, which significantly reduces the risk of fire (26).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a disproportionate increase in larger gaps can be expected to slow overall forest recovery rates and thus will have long-lasting effects on a wide range of ecological processes from carbon cycling to faunal dynamics (16,30,31). These results also highlight the value of reduced-impact logging operations that tend to minimize initial canopy damage levels and thus are more conducive to an expeditious reestablishment of ecosystem functions (15,27,32). Low-impact or low-volume logging also leaves the forest with fewer and smaller canopy gaps, which significantly reduces the risk of fire (26).…”
Section: Resultsmentioning
confidence: 99%
“…That these trees perform better, when old, far from logging gaps may be link to a greater sensitivity to environmental changes in logging gaps. For example, it has been suggested that logging gaps dry out and have lower humidity due to the direct sunlight (Olander et al. 2005), although we did not measure these environmental factors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, total P in the Costa Rican Ultisols is approximately twice that at Tapajo´s, and plant-available P fractions are also ;25% higher in the Costa Rican sites (Silver et al 2000, Olander et al 2005. For example, at the site-specific scale, foliar P is significantly higher (F ¼ 6.2, df ¼ 1, 4, P , 0.01), and foliar N:P significantly lower (F ¼ 5.6, df ¼ 1, 4, P , 0.01), across all species common to both the Costa Rican Mollisols and the neighboring Ultisols.…”
Section: Environmental Controls Over Foliar N:p Ratiosmentioning
confidence: 99%